Association between hospital volume and quality of gastric cancer surgery in the CRITICS trial. Issue 6 (13th April 2018) - Claassen, Y. H. M.; van Sandick, J. W.; Hartgrink, H. H.; Dikken, J. L.; De Steur, W. O.; van Grieken, N. C. T.; Boot, H.; Cats, A.; Trip, A. K.; Jansen, E. P. M.; Meershoek‐Klein Kranenbarg, W. M.; Braak, J. P. B. M.; et al.
Abstract : Background: Studies investigating the association between hospital volume and quality of gastric cancer surgery are lacking. In the present study, the effect of hospital volume on quality of gastric cancer surgery was evaluated by analysing data from the CRITICS (ChemoRadiotherapy after Induction chemotherapy In Cancer of the Stomach) trial. Methods: Patients who underwent gastrectomy with curative intent in the Netherlands were selected from the CRITICS trial database. Annual hospital volume of participating centres was derived from the Netherlands Cancer Registry. Hospital volume was categorized into very low (1–10 gastrectomies per year per institution), low (11–20), medium (21–30) and high (31 or more), and linked to the CRITICS database. Quality of surgery was analysed by surgicopathological compliance (removal of at least 15 lymph nodes), surgical compliance (removal of indicated lymph node stations) and the Maruyama Index. Postoperative morbidity and mortality were also compared between hospital categories. Results: Between 2007 and 2015, 788 patients were included in the CRITICS study, of whom 494 were analysed. Surgicopathological compliance was higher (86·7 versus 50·4 per cent; P  < 0·001), surgical compliance was greater (52·9 versus 19·8 per cent; P  < 0·001) and median Maruyama Index was lower (0 versus 6; P  = 0·006) in high‐volume hospitals compared with very low‐volume hospitals. There was no statistically significant difference in postoperative complications or mortality between the hospital volume categories. Conclusion: Surgery performed in high‐volume hospitals was associated with better surgical quality than surgery carried out in lower‐volume hospitals. Abstract : High volume better quality